Exploration and exploitation in early stage ventures and SMEs - Stettner, Uriel; Aharonson, Barak S.; Amburgey, Terry L. (Technology, innovation, entrepreneurship and competitive strategy series, 2014)
This volume of Technology, innovation, entrepreneurship and competitive strategy is devoted to research aimed at understanding the implications of Exploration and Exploitation activities in early-stage ventures and small-and-medium enterprises (SMEs).